“Radix Saniculae”: Phytochemical Characterization and Potential Adulteration of an Austrian Traditional Wound-Healing Agent - Elisabeth Eichenauer; Christina Sykora; Karin Ortmayr; Sabine Glasl (Plants)
The aerial parts (Herba Saniculae) and the underground parts (Radix Saniculae) of Sanicula europaea (sanicle) have been used traditionally in Austrian folk medicine to treat wounds. Interestingly, in the Austrian vernacular, “Radix Saniculae” can also refer to the underground parts of Cardamine enneaphyllos. This ambiguity can lead to mistakes in using these two plants and, importantly, adulterations. The present work aims to shed light on using Radix Saniculae as a wound-healing agent. Thus, the main components in the aerial and the scarcely investigated underground parts of Sanicula europaea were identified and compared to the underground parts of Cardamine enneaphyllos. For this purpose, different analytical techniques were employed: TLC, HPLC-DAD/ELSD, UHPLC-ESI-MS, and GC-MS. The main components in both Sanicula and Cardamine plant extracts were saccharides. Both parts of Sanicula europaea showed similar compositions: hydroxycinnamic acid derivatives and triterpene saponins. In contrast, the underground parts of Cardamine enneaphyllos contain two glucosinolates and their breakdown products. These findings suggest the same wound-healing activity for the underground parts of Sanicula europaea as was already found for its aerial parts. The glucosinolates detected in Cardamine enneaphyllos substantiate its use in wound healing. Nevertheless, the presented analytical methods allow for easy discovery of adulterations.